Thermal buckling of a free circular plate - Webber, J. P. H. (College of Aeronautics, 1960)
The buckling of a free circular plate subjected to a temperature field, which varies only in the radial direction, is considered. The problem is first investigated experimentally and the mode of deflection and form of the temperature distribution are measured. Expressions are developed for the thermal stresses and the deflection mode of the plate, which are used for a theoretical small deflection energy analysis. This solution is found to compare favourably with the experimental results.